Syncretizing Culture and Faith: The Kurang Labih Principle in Kalimantan - Apriati, Yuli; Hassan, Zainudin Bin; Nur, Rahmat; Handy, Muhammad Rezky Noor; Widaty, Cucu (KARSA Journal of Social and Islamic Culture, 2025)
This article aims to identify and analyze the value of the local wisdom â€œKurang Labihâ€ in the traditional river-based trading system, specifically as a form of local wisdom among the Banjar people. Values â€‹â€‹rooted in the local wisdom of the Banjar people, such as the value of â€œKurang Labih,â€ remain the primary foundation in the governance of their social life, especially in traditional trade practices. This research employs a qualitative approach, utilizing a case study method. Data were collected through observation, interviews, and documentation to produce a comprehensive writing on cultural phenomena. The study’s results found that the culture and local wisdom in traditional trade at this floating market possess the value of â€œKurang Labih,â€ which can make the trade process mabrur, or moral, namely a trade that prioritizes goodness, virtue, and blessings received from Allah SWT. The local wisdom of â€œKurang Labihâ€ at the Lok Baintan floating market is strongly influenced by Islamic values, considering that all traders are Muslim, and this value is passed down from generation to generation. The value â€œKurang Labihâ€ reflects the principle of caution in buying and selling, a moderate attitude, and the pursuit of blessings, thus creating acceptable trade. This value also serves as a reminder to avoid sins resulting from inaccurate weighing or defective goods, and as a means of fostering sincerity between seller and buyer. These values â€‹â€‹are in line with Islamic teachings, which have deeply influenced the cultural patterns and local wisdom of the Banjar people, particularly in the traditional river-based trading system.